A high-strength pulley for vehicle and its processing technology
By adding specific alloy elements to the HT250 cast iron of automotive pulleys and preparing high-entropy alloy coatings, the problem of insufficient strength and wear resistance of existing automotive pulleys is solved, and higher strength, hardness and wear resistance are achieved meets the needs of modern industrial production.
Patent Information
- Application Number
- CN202310432146.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-04-21
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2043-04-21
AI Technical Summary
The existing automotive pulleys have low strength, poor plasticity, poor wear resistance and short service life, which cannot meet the needs of modern industrial production.
采用废钢、增碳剂、增硫剂、硅铁和锰、钨合金元素的方法生产HT250铸铁,并在其表面制备高熵合金涂层,通过冷喷涂法进行加工。
It significantly improves the comprehensive performance of cast iron, including strength, hardness and wear resistance, extends service life, reduces production costs, and realizes the reuse of resources.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention belongs to the field of metal casting, and in particular relates to a high-strength pulley for a vehicle and a processing technology thereof. Background Art
[0002] Pulleys are important parts in automobiles, and the manufacturing process is generally based on casting and forging. In daily life, they are used in large quantities, so every 1% reduction in scrap rate in production can bring great economic benefits. Common pulleys are cast in cast iron, such as traditional cast iron of material grades HT200 and HT250. Although pulleys made of traditional cast iron are cheap and can be used, they have defects such as low strength, poor plasticity, poor wear resistance, and short service life, which can no longer meet the needs of modern industrialized production. Therefore, we propose a high-strength pulley for automobiles and its processing technology. Summary of the invention
[0003] The object of the present invention is to provide a high-strength pulley for a vehicle and a processing technology thereof, so as to solve the problems raised in the above-mentioned background technology.
[0004] In order to solve the above technical problems, the present invention provides the following technical solutions:
[0005] A processing technology for a high-strength pulley for a vehicle comprises the following steps:
[0006] S1: various raw materials of the pulley are added into the smelting furnace in the order of scrap steel briquettes, 1 / 2 component mass of carburizer, scrap steel briquettes, HT250 iron briquettes, remaining carburizer, sulfurizer, recycled materials, ferrosilicon, ferromanganese and ferrotungsten for smelting, and alloy liquid is obtained after taking out of the furnace;
[0007] S2: Add silicon-barium inoculant into the ladle, pour in alloy liquid, perform inoculation treatment, and obtain molten iron;
[0008] S3: pouring the molten iron, adding silicon-barium inoculant during pouring, and performing flow inoculation treatment to obtain HT250 castings;
[0009] S4: A high entropy alloy coating is prepared on the surface of HT250 cast iron by cold spraying, and then mechanical processing is performed according to the design to obtain the high-strength pulley for the vehicle.
[0010] Further, the raw materials of the pulley have the following weight parts:
[0011] 35-45 parts of scrap steel briquettes, 15-20 parts of scrap steel blocks, 20-30 parts of HT250 iron briquettes, 20-30 parts of recycled materials, 2-3 parts of recarburizer, 0.07-0.1 parts of sulfurizer, 0.5-1 parts of ferromanganese, 0.5-1 parts of ferrosilicon, and 0.5-1 parts of ferrotungsten.
[0012] Furthermore, the scrap steel chip briquetting uses steel chips (oil-free and cutting fluid-free) from 45# steel workpieces to be extruded into steel blocks of uniform size (300mm long×300mm wide×10mm thick) through a briquetting machine, and the extrusion pressure is 100-125MPa.
[0013] Furthermore, the scrap steel block is made of No. 45 steel block and is rust-free.
[0014] Furthermore, the HT250 iron chip briquetting uses iron chips (oil-free and cutting fluid-free) produced after HT250 casting processing, which are extruded into cylindrical blocks of uniform size (φ80mm×80mm) by a briquetting machine, and the extrusion molding pressure is 160-220MPa.
[0015] Furthermore, the recarburizer is a semi-graphitized petroleum coke recarburizer with a carbon content of 98.5% to 99.5%.
[0016] Furthermore, the sulfur-increasing agent is iron sulfide with a sulfur content of 42% to 45%.
[0017] Furthermore, in step S1, the smelting temperature is 1525-1600°C, and the furnace temperature is 1450-1500°C.
[0018] Furthermore, in step S2, the particle size of the silicon-barium inoculant is 3-5 mm, and the amount added is 0.1%-0.3% of the mass of the alloy liquid.
[0019] Furthermore, the pouring temperature in step S3 is 1360-1400°C.
[0020] Furthermore, in step S3, the particle size of the silicon-barium inoculant is 0.3-0.7 mm, and the amount added is 0.05%-0.1% of the mass of the molten iron.
[0021] Furthermore, the process for preparing the high entropy alloy coating in step S4 is as follows:
[0022] (1) Preparation of high entropy alloy powder: Select W, Re, Nb, Ti, Ta, Pt single metal powders and load them into a ball mill, add high hardness balls, seal and fill with protective gas, perform mechanical ball milling, and mix them evenly to obtain high entropy alloy powder;
[0023] (2) Preparation of high-entropy alloy coating: First, the surface of HT250 cast iron is cleaned, degreased, and derusted. Then, the high-entropy alloy powder is accelerated to 500-1200 m / s through a cold spray device using helium as the accelerating gas flow. The powder particles are sprayed on the treated HT250 cast iron surface in a fully solid state far below the melting point of the material. Finally, it is heat treated at a temperature of 500-800°C for 1-2 h to obtain a high-entropy alloy coating with a thickness of 0.5-1 mm.
[0024] Furthermore, in step (1), the high entropy alloy powder has the following weight proportions: W is 30 to 32 parts, Re is 5 to 8 parts, Nb is 20 to 25 parts, Ti is 10 to 13 parts, Ta is 13 to 16 parts, and Pt is 5 to 10 parts.
[0025] Furthermore, in step (1), the average particle size of the high entropy alloy powder is 35 to 40 μm.
[0026] Furthermore, the cold spraying equipment in step (2) includes the following process parameters: gas parameters: pressure of 4.0-8.0 MPa, temperature of 300-500° C.; nozzle parameters: the distance between the nozzle and the workpiece surface is 10-15 mm, the nozzle movement speed is 300-500 mm / min, and the scanning interval is 2-3 mm.
[0027] Compared with the prior art, the present invention has the following beneficial effects:
[0028] 1. A high-strength pulley for a vehicle and a processing technology thereof of the present invention adopts a method of adding a carbon enhancer, a sulfur enhancer, ferrosilicon, manganese and tungsten alloy elements to scrap steel to produce HT250 cast iron, which can greatly improve the comprehensive performance of cast iron. Scrap steel is cheap, which reduces production costs and realizes the reuse of resources. Scrap steel contains a certain amount of nitrogen and manganese. Nitrogen can change the graphite structure in the cast iron organization to prevent the formation of ferrite and promote the formation of pearlite. Manganese can stabilize pearlite and carbide and increase the content of pearlite. Carbon enhancer can improve the graphitization ability of molten iron, and the molten iron is purer, which can prevent or reduce the shrinkage tendency. Sulfur can reduce the solubility of carbon in iron, enhance the activity of carbon, and form MnS compounds with manganese. It not only has no effect on graphitization, but also can serve as a non-spontaneous crystal nucleus for graphitization, promote the graphitization of cast iron, and improve the graphite morphology. Silicon, like carbon, can promote graphitization. Manganese and tungsten alloy elements, an appropriate amount of manganese helps to generate texture structure, increase strength and wear resistance, and can also neutralize sulfur to achieve the effect of desulfurization. Tungsten and carbon form tungsten carbide with high hardness and wear resistance, which is beneficial to improve the tensile strength and hardness of cast iron.
[0029] 2. A high-strength pulley for automobiles and its processing technology of the present invention utilizes cold spraying to prepare a high-entropy alloy coating on the surface of HT250 cast iron, thereby improving the strength, hardness and wear resistance of the cast iron surface. Cold spraying is an emerging metal spraying process. During the spraying process, no high-energy beam heat source is required. The raw material powder is deposited on the surface of the substrate by high strain rate plastic deformation in a fully solid state. It not only retains the microstructure and various properties of the raw material powder to the greatest extent, but also fundamentally avoids the adverse effects of the "high temperature" preparation process. In addition, the cold spraying has a high working efficiency and can be used for the preparation of large-size components.
[0030] 3. A high-strength pulley for a vehicle and its processing technology of the present invention, a high-entropy alloy coating prepared by using W, Re, Nb, Ti, Ta, Pt single metal powder has the characteristics of high strength, high hardness, high wear resistance, high oxidation resistance, high corrosion resistance, etc. W and Re are mechanically ball milled to form a W-Re alloy. Compared with pure W, the W-Re alloy has the advantages of better high temperature resistance, ductility, and good low temperature performance; similarly, the formed Nb-W alloy has the advantages of oxidation resistance, high temperature resistance, etc.; the formed Nb-Ti alloy has the advantages of high strength, good corrosion resistance and good wear resistance; adding Ta and Pt can improve the coating diffusion problem and improve the comprehensive performance of the coating. DETAILED DESCRIPTION
[0031] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0032] In this embodiment, the scrap steel scraps are steel scraps of 45 steel workpieces, with a carbon content of 0.45%, a silicon content of 0.28, a manganese content of 0.6%, a chromium content of 0.05%, and a sulfur content of 0.3%, provided by Yongkang Jingzhen Mould Material Co., Ltd.; the scrap steel block is a 45 steel block: with a carbon content of 0.45%, a silicon content of 0.28, a manganese content of 0.6%, a chromium content of 0.05%, and a sulfur content of 0.3%, provided by Suzhou Teyi Metal Material Co., Ltd.; HT250 iron scrap briquette: with a carbon content of 3.2% , silicon content is 1.8%, manganese content is 0.9%, sulfur content is 0.05%, provided by Shanghai New Ruisi New Energy Technology Co., Ltd.; recycled materials are provided by Wuxi Chengyi Lian Stainless Steel Co., Ltd.; carburizer: carbon content is 98.5%~99.5%, specification is 1~5 mesh, provided by Anyang Jinyao Metallurgical Co., Ltd.; sulfurizer is iron sulfide: sulfur content is 42%~45%, specification is 20~325 mesh, provided by Lingshou County Zeming Mineral Products Processing Plant; ferrosilicon: silicon content is 72%~75%, provided by Lingshou County Long Provided by Tong Building Materials Factory; ferromanganese: manganese content is 80%~85%, provided by Anyang Huatuo Metallurgical Co., Ltd.; ferrotungsten: tungsten content is 75%~85%, provided by Linyi Shanyuan Ferroalloy Co., Ltd.; silicon-barium inoculant: barium content is 2~4%, provided by Anyang Jinsheng Metallurgical Materials Co., Ltd.; W single substance powder: purity ≥99.9%, specification is 270-800 mesh, provided by Tianjin Liz Technology Co., Ltd.; Re single substance powder: purity ≥99.9%, specification is 270-800 mesh, provided by Tianjin Liz Technology Co., Ltd.; Nb single substance powder: purity ≥99.9%, specification 100-300 mesh, provided by Qinghe County Fengye Metal Materials Co., Ltd.; Ti single substance powder: purity ≥99.9%, specification 270-800 mesh, provided by Tianjin Liz Technology Co., Ltd.; Ta single substance powder: purity ≥99.9%, specification 100-400 mesh, provided by Beijing Xingrongyuan Technology Co., Ltd.; Pt single substance powder: purity ≥99.9%, specification 300 mesh, provided by Beijing Xingrongyuan Technology Co., Ltd.
[0033] In the following examples one portion is equal to 200 g.
[0034] Embodiment 1: A processing technology for a high-strength pulley for a vehicle, comprising the following processes:
[0035] S1: various raw materials of the pulley are added into a large vacuum induction melting furnace in the order of 35 parts of scrap steel briquettes, 1 part of carburizer, 15 parts of scrap steel briquettes, 20 parts of HT250 iron briquettes, 1 part of remaining carburizer, 0.07 parts of sulfurizer, 20 parts of recycled materials, 0.5 parts of ferrosilicon, 0.5 parts of ferromanganese, and 0.5 parts of ferrotungsten for melting, and alloy liquid is obtained after taking out of the furnace;
[0036] S2: Add 0.09 parts of 3mm silicon-barium inoculant into the bag, pour in the alloy liquid, perform inoculation treatment, and obtain molten iron;
[0037] S3: pouring the molten iron, adding 0.05 parts of 0.2 mm silicon-barium inoculant during pouring, and performing inoculation treatment to obtain HT250 castings;
[0038] S4: A high entropy alloy coating is prepared on the surface of HT250 cast iron by cold spraying, and then mechanical processing is performed according to the design to obtain the high-strength pulley for the vehicle.
[0039] The process for preparing the high entropy alloy coating in step S4 is as follows:
[0040] (1) Preparation of high entropy alloy powder: 30 parts of W, 5 parts of Re, 20 parts of Nb, 10 parts of Ti, 13 parts of Ta, and 5 parts of Pt single metal powders were loaded into a ball mill, high hardness balls were added, the mill was sealed and filled with protective gas, and mechanical ball milling was performed. After mixing evenly, a high entropy alloy powder with an average particle size of 35 μm was obtained;
[0041] (2) Preparation of high-entropy alloy coating: The surface of HT250 cast iron was first cleaned, degreased, and derusted. Then, the high-entropy alloy powder was accelerated to 500 m / s using helium as the accelerating gas flow through a cold spraying device. The powder particles were sprayed onto the treated HT250 cast iron surface in a fully solid state far below the melting point of the material. Finally, it was heat treated at 500 °C for 1 h to obtain a high-entropy alloy coating with a thickness of 0.5 mm.
[0042] The cold spray equipment includes the following process parameters: gas parameters: pressure is 4.0MPa, temperature is 300°C; nozzle parameters: the distance between the nozzle and the workpiece surface is 10mm, the nozzle moving speed is 300mm / min, and the scanning interval is 2mm.
[0043] Embodiment 2: A processing technology for a high-strength pulley for a vehicle, comprising the following processes:
[0044] S1: various raw materials of the pulley are added into a large vacuum induction melting furnace in the order of 40 parts of scrap steel briquettes, 1.2 parts of carburizer, 17 parts of scrap steel briquettes, 25 parts of HT250 iron briquettes, 1.2 parts of remaining carburizer, 0.09 parts of sulfurizer, 25 parts of recycled materials, 0.75 parts of ferrosilicon, 0.75 parts of ferromanganese, and 0.75 parts of ferrotungsten for melting, and alloy liquid is obtained after taking out of the furnace;
[0045] S2: Add 0.23 parts of 4mm silicon-barium inoculant into the bag, pour in the alloy liquid, perform inoculation treatment, and obtain molten iron;
[0046] S3: pouring the molten iron, adding 0.09 parts of 0.4 mm silicon-barium inoculant during pouring, and performing inoculation treatment to obtain HT250 castings;
[0047] S4: A high entropy alloy coating is prepared on the surface of HT250 cast iron by cold spraying, and then mechanical processing is performed according to the design to obtain the high-strength pulley for the vehicle.
[0048] The process for preparing the high entropy alloy coating in step S4 is as follows:
[0049] (1) Preparation of high entropy alloy powder: 31 parts of W, 7 parts of Re, 23 parts of Nb, 11 parts of Ti, 14 parts of Ta, and 8 parts of Pt single metal powders were loaded into a ball mill, high hardness balls were added, the mill was sealed and filled with protective gas, and mechanical ball milling was performed. After mixing evenly, a high entropy alloy powder with an average particle size of 36 μm was obtained;
[0050] (2) Preparation of high-entropy alloy coating: The surface of HT250 cast iron was first cleaned, degreased, and derusted. Then, the high-entropy alloy powder was accelerated to 900 m / s using helium as the accelerating gas flow through a cold spraying device. The powder particles were sprayed onto the treated HT250 cast iron surface in a fully solid state far below the melting point of the material. Finally, it was heat treated at 600 °C for 1.5 h to obtain a high-entropy alloy coating with a thickness of 1 mm.
[0051] The cold spray equipment includes the following process parameters: gas parameters: pressure is 6.0MPa, temperature is 400°C; nozzle parameters: the distance between the nozzle and the workpiece surface is 13mm, the nozzle moving speed is 400mm / min, and the scanning interval is 2mm.
[0052] Embodiment 3: A processing technology for a high-strength pulley for a vehicle, comprising the following processes:
[0053] S1: various raw materials of the pulley are added into a large vacuum induction melting furnace in the order of 45 parts of scrap steel briquettes, 1.5 parts of carburizer, 20 parts of scrap steel briquettes, 30 parts of HT250 iron briquettes, 1.5 parts of remaining carburizer, 0.1 parts of sulfurizer, 30 parts of recycled materials, 1 part of ferrosilicon, 1 part of ferromanganese, and 1 part of ferrotungsten for smelting, and alloy liquid is obtained after taking out of the furnace;
[0054] S2: Add 0.39 parts of 5mm silicon-barium inoculant into the bag, pour in the alloy liquid, perform inoculation treatment, and obtain molten iron;
[0055] S3: pouring the molten iron, adding 0.13 parts of 0.8 mm silicon-barium inoculant during pouring, and performing inoculation treatment to obtain HT250 castings;
[0056] S4: A high entropy alloy coating is prepared on the surface of HT250 cast iron by cold spraying, and then mechanical processing is performed according to the design to obtain the high-strength pulley for the vehicle.
[0057] The process for preparing the high entropy alloy coating in step S4 is as follows:
[0058] (1) Preparation of high entropy alloy powder: 32 parts of W, 8 parts of Re, 25 parts of Nb, 13 parts of Ti, 16 parts of Ta, and 10 parts of Pt single metal powders are loaded into a ball mill, high hardness balls are added, the mill is sealed and filled with protective gas, and mechanical ball milling is performed. After mixing evenly, a high entropy alloy powder with an average particle size of 40 μm is obtained;
[0059] (2) Preparation of high-entropy alloy coating: The surface of HT250 cast iron was first cleaned, degreased, and derusted. Then, the high-entropy alloy powder was accelerated to 1200 m / s using helium as the accelerating gas flow through a cold spraying device. The powder particles were sprayed onto the treated HT250 cast iron surface in a fully solid state far below the melting point of the material. Finally, it was heat treated at 800 °C for 2 h to obtain a high-entropy alloy coating with a thickness of 1 mm.
[0060] The cold spray equipment includes the following process parameters: gas parameters: pressure is 8.0MPa, temperature is 500°C; nozzle parameters: the distance between the nozzle and the workpiece surface is 15mm, the nozzle moving speed is 500mm / min, and the scanning interval is 3mm.
[0061] Comparative Example 1: A processing technology for a high-strength pulley for a vehicle, comprising the following processes:
[0062] Compared with Example 2, no ferromanganese and ferrotungsten are added in step S1 of Comparative Example 1; the other steps are the same as those of Example 2.
[0063] Comparative Example 2: A processing technology for a high-strength pulley for a vehicle, comprising the following processes:
[0064] Compared with Example 2, during the pouring of Comparative Example 2, no silicon-barium inoculant was added, and no inoculant treatment was performed; the other steps were the same as those of Example 2.
[0065] Comparative Example 3: A processing technology for a high-strength pulley for a vehicle, comprising the following processes:
[0066] Compared with Example 2, in Comparative Example 3, the process for preparing the high entropy alloy coating is deleted, and the surface of the HT250 cast iron is not sprayed; the other steps are the same as those in Example 2.
[0067] Comparative Example 4: A processing technology for a high-strength pulley for a vehicle, comprising the following processes:
[0068] Compared with Example 2, in Comparative Example 4, the W, Re, Nb, Ti, Ta, and Pt single-element metal powders are not subjected to mechanical ball milling; the other steps are the same as those in Example 2.
[0069] experiment
[0070] The pulleys obtained in Examples 1-3 and Comparative Examples 1-4 were taken to prepare samples, and their performances were tested and the test results were recorded. The results are shown in Table 1:
[0071] According to GB / T 231.1-2018 "Brinell Hardness Test for Metallic Materials", the hardness is measured. The experimental steps are as follows: pre-treat the surface of the sample, the surface should be smooth and flat, and there should be no oxides, dirt or grease. The surface of the sample should be able to ensure the accurate measurement of the indentation diameter, and the surface roughness Ra should generally not be less than 0.80μm. The thickness of the sample should be at least 10 times the depth of the indentation. The test is carried out at room temperature (25±2℃), with a 10mm steel ball or carbide ball pressed into the surface of the sample under a test force of 3000N. After the specified holding time (10-15s), the test force is removed and the diameter of the indentation on the surface of the sample is measured. The Brinell hardness value is the quotient of the test force divided by the surface area of the indentation.
[0072] According to GB / T 228.1-2021 "Tensile Test of Metallic Materials Part 1: Room Temperature Test Method", the tensile strength is determined. The experimental steps are as follows: a 250mm long × 30mm wide specimen is made, and tensile tests are performed on specimens of the same size, specifications and shape. Use a grading machine to engrave a circular line within the original gauge range, and divide the gauge range into 10 equal-length grids. The original diameter is measured to be 10mm, and the original gauge length is 100mm. Manually control the upper chuck to a suitable clamping position. Select a suitable force gauge. Start the test machine and raise the workbench by about 10mm to eliminate the influence of the deadweight of the workbench system. Adjust the active pointer to zero, bring the driven pointer close to the active pointer, and adjust the automatic drawing device. First clamp the specimen in the upper chuck, then move the lower chuck to a suitable clamping position, and finally clamp the lower end of the specimen. Check the completion of the above steps. Start the test machine, preload a small amount of load (the stress corresponding to the load cannot exceed the proportional limit of the material), and then unload to zero to check whether the test machine is working properly. Conduct the test, start the testing machine, load slowly and evenly, and carefully observe the rotation of the force measuring pointer and the drawing of the graph by the plotting device. Pay attention to capturing the yield load value and record it to calculate the yield point stress value. Pay attention to the slip phenomenon in the yield stage. After the yield stage, the loading speed can be faster. When the maximum value is about to be reached, pay attention to the "necking" phenomenon. Stop the machine immediately after the specimen breaks and record the maximum load value. Remove the specimen and the recording paper. Use a vernier caliper to measure the gauge length after breaking and the minimum diameter at the necking point.
[0073] Table 1: Performance test of high-strength pulleys for vehicles in Examples 1-3 and Comparative Examples 1-4
[0074]
[0075] According to the data in the above table, we can clearly draw the following conclusions:
[0076] 1. Compared with Examples 1-3, the hardness and tensile strength of the product obtained in Comparative Example 1 are both reduced, indicating that the appropriate addition of manganese and tungsten alloy elements not only helps to generate texture structure, increase strength and wear resistance, but also helps to improve the tensile strength and hardness of cast iron.
[0077] 2. Compared with Comparative Example 2, the hardness of the product obtained by Implementation 1-3 is significantly increased. It can be seen that the in-stream inoculation in the present invention can improve the quality of molten iron, enhance the nucleation ability of molten iron, and improve the hardness of the product.
[0078] 3. Compared with Examples 1-3, the hardness and tensile strength of the products obtained in Comparative Examples 3 and 4 are reduced, indicating that the preparation of a high entropy alloy coating on the surface of HT250 cast iron improves the tensile strength, hardness and wear resistance of the cast iron surface; compared with the product obtained from the elemental metal powder that has not been mechanically ball milled, the mechanical properties of the product obtained from the elemental metal powder after mechanical ball milling have been significantly improved.
[0079] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process method article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process method article or device.
[0080] Finally, it should be noted that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A processing technology for a high-strength pulley for a vehicle, characterized in that: The following steps are involved: S1: various raw materials of the pulley are added into the smelting furnace in the order of scrap steel briquettes, 1 / 2 weight portion of carburizer, scrap steel briquettes, HT250 iron briquettes, the remaining portion of carburizer, sulfurizer, recycled materials, ferrosilicon, ferromanganese and ferrotungsten for smelting, and alloy liquid is obtained after taking out of the furnace; S2: Add silicon-barium inoculant into the ladle, pour in alloy liquid, perform inoculation treatment, and obtain molten iron; S3: pouring the molten iron, adding silicon-barium inoculant during pouring, and performing flow inoculation treatment to obtain HT250 castings; S4: preparing a high entropy alloy coating on the surface of the HT250 casting by cold spraying, and then performing mechanical processing according to the design to obtain the high-strength pulley for the vehicle; The process for preparing the high entropy alloy coating in step S4 is as follows: (1) Preparation of high entropy alloy powder: Select W, Re, Nb, Ti, Ta, Pt single metal powders and load them into a ball mill, add high hardness balls, seal and fill with protective gas, perform mechanical ball milling, and mix them evenly to obtain high entropy alloy powder; (2) Preparation of high-entropy alloy coating: First, the surface of the HT250 casting is cleaned, degreased, and derusted. Then, the high-entropy alloy powder is accelerated to 500-1200 m / s by cold spraying equipment using helium as the accelerating gas flow. The powder particles are sprayed on the treated surface of the HT250 casting in a fully solid state far below the melting point of the material. Finally, it is heat treated at a temperature of 500-800°C for 1-2 hours to obtain a high-entropy alloy coating with a thickness of 0.5-1 mm. The high entropy alloy powder in step (1) has the following weight proportions: 30 to 32 parts of W, 5 to 8 parts of Re, 20 to 25 parts of Nb, 10 to 13 parts of Ti, 13 to 16 parts of Ta, and 5 to 10 parts of Pt; The raw materials of the pulley have the following weight parts: 35-45 parts of scrap steel briquettes, 15-20 parts of scrap steel briquettes, 20-30 parts of HT250 iron briquettes, 20-30 parts of recycled materials, 2-3 parts of carburizer, 0.07-0.1 parts of sulfurizer, 0.5-1 parts of ferromanganese, 0.5-1 parts of ferrosilicon, and 0.5-1 parts of ferrotungsten; In step S2, the particle size of the silicon-barium inoculant is 3-5 mm, and the amount added is 0.1%-0.3% of the mass of the alloy liquid; In step S3, the particle size of the silicon-barium inoculant is 0.2-0.8 mm, and the amount added is 0.05%-0.1% of the mass of the molten iron.
2. The processing technology of a high-strength pulley for a vehicle according to claim 1 is characterized in that: In step S1, the smelting temperature is 1525-1600°C, and the furnace temperature is 1450-1500°C.
3. The processing technology of a high-strength pulley for a vehicle according to claim 1 is characterized in that: The pouring temperature in step S3 is 1360-1400°C.
4. The processing technology of a high-strength pulley for a vehicle according to claim 1 is characterized in that: In step (2), the cold spraying equipment includes the following process parameters: gas parameters: pressure of 4.0-8.0 MPa, temperature of 300-500° C.; nozzle parameters: the distance between the nozzle and the workpiece surface is 10-15 mm, the nozzle moving speed is 300-500 mm / min, and the scanning interval is 2-3 mm.
5. A high-strength pulley for a vehicle made according to the processing technology described in any one of claims 1 to 4.
Citation Information
Patent Citations
HT250 casting and production method thereof
CN104060155A
Cold spraying
US20210207271A1
Process method for preparing high-hardness corrosion-resistant hub coating
WO2022109993A1